(untitled) (The Pakistan Development Review, 1994)
The emerging trend of focussing more and more attention on improving the production and productivity of farming in Pakistan has prompted bankers to evolve better schemes to improve the income generation capacity of the farming community and help them repay the borrowed funds in time. This can be called a step in the right direction. The Agriculture Development Bank of Pakistan (ADBP) the Federal Bank for Cooperatives (FBC) and the Commercial Banks are the major formal institutions, which because being Government owned have in fact become the agents for rural development purveying the most important input i.e. credit. Hence, the expansion and growth of the banking sector have become synonymous with national welfare. The main objective of banks in lending is to improve the recycling of funds capability borrowed from the public or raised from internal or external sources for the benefit of society. The recovery of loans portrays a dismal picture. Since agricultural lending expanded extensively, the recovery percentage has received a great setback due to which as per estimate more than half of the funds are not funnelled back. In fact, financial distress has always been a feature of the financial scene but most of the time it has been associated with being a sectoral problem such as those affecting agriculture and industries.